Lean management implementation difficulties, studies and recommendations - Jouhri, Mohammed; Soulhi, Aziz (International Journal of Engineering and Technology, 2020)
Speeding up FAST FASHION development cycles for the apparel industry, always bringing more values to the customer, seeking perfor-mance through continuous improvement. This paper presents a deployment approach to Lean Management, helping to make it more con-crete, efficient, less theoretical. The realization of the approach was based on case studies, state of art and references made in Moroccan companies in the textile and clothing sector. This analysis sheds light on the importance of aligning the lean management strategy with the company's strategy and values, hence the use of the socio-technical approach. The objective of this study is to realize a brief application of Lean Management, able to transform it from a theoretical organization to a practical one. This Lean Deployment Study is considered unique in that it addresses the need to work on psychology, culture, societal values of each company, to prepare for and align it with Lean manage-ment strategy, before attacking its practices. This article is a first development of strategies and methodologies proposed for improvements that seek to focus on the overall performance of the company.Â